The Impact of Social Factors, Family Economics, and Motivation on Fifth Grade IPAS Learning Achievement - Ulfa Wilda; Elpisah Elpisah; Husain Husain (Educational Dynamics: International Journal of Education and Social Sciences, 2025)
This study aims to examine the impact of social status, family economic conditions, and student motivation on the learning achievement of fifth-grade students at SD Negeri 26 Matekko, located in the Kecamatan Gantarang of Kabupaten Bulukumba. The research employed a quantitative Ex Post Facto design, collecting data from 45 students using questionnaires, observations, and literature studies. The analysis involved multiple regression to explore the relationships between the variables. The findings indicate that all three factors—social status, family economic conditions, and student motivation—positively and significantly affect learning achievement. Notably, social status emerged as the most influential factor. These results suggest the need for targeted interventions addressing socio-economic disparities and enhancing student motivation. Future research should consider a broader range of variables and a longitudinal approach.